Technological Perspective for Use the Natural Pineapple Fiber in Mortar to Repair Structures - de Azevedo, Afonso R. G.; Marvila, Markssuel Teixeira; Antunes, Maria Lucia P. [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Fediuk, Roman (Springer Nature, 2021)
Abstract: The use of natural fiber in cementitious materials can contribute to the improvement of technological properties and environmental issues related to the reuse of agro-industrial waste. World pineapple production is approximately 12.8 million tons per year, generating large environmental impacts, because the disposal natural fibers in landfills. The objective of this research was to evaluate the potential of reusing the natural fiber from the pineapple crown as a reinforcement element in eco-friendly mortar for the purpose of recovering building structures committed to coastal environments, evaluating the influence of the fiber surface treatment process with NaOH and its durability in laboratory conditions, in addition to avoiding the disposal of this waste in landfills. The natural fibers were characterized physically, morphologically and chemically, in the treated and untreated (natural) condition, for further technological evaluation of mortars in the fresh state, such as consistency, specific mass, incorporated air and water retention. Comprehensive studies of the hardened state were also carried out to study mechanical strength (compressive, flexural and tensile), water absorption due to capillarity and immersion, as well as durability by evaluating mass loss and mechanical strength after exposure conditions. The results showed that the fiber treatment process improved its characteristics for application in mortar with addition of 2.5% fiber treated in cement mass, causing the better in the technological and durability properties, and a proposed new means of disposing of agro-industrial waste, contributing to a circular economy. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: Agro-industrial waste; Natural fiber; Reinforced